Teaching Russian students to analyze the syntactic structure of sentences in modern Chinese (Mandarin) - Arseniy V. Skvortsov; Oksana A. Malykh (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper deals with methodological issues of teaching senior students of language universities to analyze the syntactic structure of sentences in modern Chinese at the phrase level. The technology of teaching Russian students to analyze the syntactic structure of sentences in modern Chinese is presented in the following stages: 1) theoretical explanation of the classification of phrases in modern Chinese and methods of mastering this phenomenon by students; 2) introduction to five different ways of syntactic analysis of sentences at the phrase level; 3) presentation of features of the analysis "from small to large"; 4) improvement of skills of independent analysis of offers by students using the specified method. Much attention is paid to the order of establishment of relations between lexical items in phrases, combined with each other semantically. At the same time, in the developed technology, it is recommended to analyze the group of subject and predicate separately, performing an analysis from right to left. When faced with more difficult cases - long complicated sentences, the authors recommend analyzing the sentence in both directions, both from left to right and from right to left. Russian translation is recommended when determining the type of a phrase in Chinese. It is recommended that you translate the phrase into Russian, set its type in Russian, and then make a conclusion about the type of this phrase based on the typology used in Chinese. The existing limitations of using this method are discussed. As the main method of analyzing the syntactic structure of Chinese sentences, the analysis "from small to large" is chosen as the most convenient in implementation and allows parsing long complicated sentences.